Penyuluhan Pada Ibu Nifas Mengenai Perawatan Tali Pusat Di Desa Ruta - Rusnani Martahan; Sukma Kabau (Poltekkes Kemenkes Denpasar, 2019)
The umbilical cord is the main entry point for systemic infections in newborns. In general, umbilical cord care aims to prevent infection and accelerate the breakdown of the umbilical cord. Basically, umbilical cord infection can be prevented by doing good and correct umbilical cord care, namely with the principle of dry and clean care. Many opinions about the best way to care for the umbilical cord. One of the efforts that can be made to reduce infant morbidity and mortality is by providing effective health services to the community regarding the care of the baby's umbilical cord. In carrying out these efforts, human resources who have the ability to provide quality services are needed, namely by providing health education to the community, so that the knowledge possessed by the community is expected to influence people's behavior towards healthKeywords: Childbirth, Umbilical Cord Care.